The Origin of the Subtropical Coral Alveopora japonica (Scleractinia: Acroporidae) in High-Latitude Environments - Kang, Ji Hyoun; Jang, Ji Eun; Kim, Jae Hwan; Kim, Sangil; Keshavmurthy, Shashank; Agostini, Sylvain; Reimer, James D.; Chen, Chaolun Allen; Choi, Kwang-Sik; Park, Sang Rul; Lee, Hyuk Je (Frontiers in Ecology and Evolution, 2020)
Marine ecosystems in temperate regions have been significantly affected by rising seawater temperatures due to climate change. Alveopora japonica, a small zooxanthellate scleractinian coral, occurs in the northwestern Pacific including Taiwan, Japan, and Jeju Island in Korea. The northern populations around Jeju Island have recently undergone rapid growth in numbers, with negative impacts on local biodiversity. However, it is unclear whether these Korean populations occurred historically and where they originate from. In this study, we investigated the phylogenetic relationships of A. japonica along with its endosymbiont Symbiodiniaceae across five geographic regions, including Jeju Island in Korea, Taiwan, and Japan. Nuclear internal transcribed spacer (ITS) sequences revealed unexpected species-level divergence among three distinct phylogenetic clusters (Korea, Taiwan, Japan) with no sharing of haplotypes among lineages, suggesting these may each represent cryptic species in Alveopora. 23S ribosomal DNA of Symbiodiniaceae showed two well-separated phylogenetic clusters, in which Korean and Japanese symbionts shared the same clade and Taiwanese ones formed a distinct clade. Given the deep phylogenetic divergences among the lineages for both corals and Symbiodiniaceae, the Korean populations appear to have existed for a long evolutionary time period rather than representing a poleward migration from subtropical environments following recent climate change. Our study highlights cryptic species diversity in Alveopora at high-latitude environments.